A score that predicts 1-year functional status in patients with anti-NMDA receptor encephalitis. (15th January 2019) - Balu, Ramani; McCracken, Lindsey; Lancaster, Eric; Graus, Francesc; Dalmau, Josep; Titulaer, Maarten J.
Abstract : Objective: To construct a grading score that predicts neurologic function 1 year after diagnosis of anti-NMDA receptor (NMDAR) encephalitis. Methods: Three hundred eighty-two patients with detailed information and functional status at 1 year were studied. Factors associated with poor status (defined as modified Rankin Scale score ≥3) were identified and incorporated into a multivariate logistic regression model. This model was used to develop a 5-point prediction score, termed the anti-NMDAR Encephalitis One-Year Functional Status (NEOS) score. Results: Intensive care unit admission ( p < 0.001), treatment delay >4 weeks ( p = 0.012), lack of clinical improvement within 4 weeks ( p < 0.001), movement disorder ( p = 0.001), central hypoventilation ( p < 0.001), elevated CSF white blood cell count ( p < 0.001), elevated CSF protein level ( p = 0.027), and abnormal MRI ( p = 0.002) were associated with 1-year functional status in univariate analysis. Intensive care unit admission, treatment delay >4 weeks, lack of clinical improvement within 4 weeks, abnormal MRI, and CSF white blood cell count >20 cells/μL were independent predictors for outcome in multivariate regression modeling. These 5 variables were assigned 1 point each to create the NEOS score. NEOS score strongly associated with the probability of poor functional status at 1 year (3% for 0 or 1 point to 69% for 4 or 5 points, p < 0.001). Conclusions: The NEOS score accurately predicts 1-year functional status in patients with anti-NMDAR encephalitis. This score could help estimate the clinical course following diagnosis and may aid in identifying patients who could benefit from novel therapies.